Composite graphite material, preparation method and application thereof and lithium ion battery

By formulating the cover layer connected to the co -price bond between the surface of the graphite material and the lif, the problem of the existing graphite material in the lithium ion battery is poorly reconciled and the first effect is poor. Chemical performance and simpler preparation process.

CN119361650APending Publication Date: 2025-01-24SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411547922.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When the existing graphite material is used as the negative electrode material of lithium-ion batteries, the circulation performance and first-term effect are poor, the preparation process is complicated, and the coating uniformity is poor.

Method used

Lithium fluoroalkylsulfonimide and biomass carbon are used to generate a coating agent through a solvothermal reaction, which is then mixed with graphite and carbonized to form a coating layer that is covalently connected between hard carbon and LiF.

Benefits of technology

Improve the conductivity and mechanical stability of graphite materials, inhibit volume expansion, significantly improve the first effect and circulation performance of lithium -ion batteries, and the preparation method is simple and easy to industrialized production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361650A_ABST
    Figure CN119361650A_ABST
Patent Text Reader

Abstract

The invention discloses a composite graphite material and a preparation method and application thereof and a lithium ion battery, the composite graphite material comprises graphite, the surface of the graphite is provided with a coating layer, the coating layer comprises hard carbon and LiF, and the hard carbon and the LiF are connected through a covalent bond. The preparation method of the composite graphite material comprises the following steps: S1, carrying out mixed solvent thermal reaction on a mixture containing fluoroalkyl sulfonimide lithium, biomass charcoal and a solvent under a subcritical condition, and filtering to obtain filtrate, namely a coating agent; s2, mixing the coating agent with graphite to obtain a precursor; the mass ratio of the coating agent to the graphite is 1: (5-50); s3, performing carbonization treatment on the precursor, thereby obtaining the product. The composite graphite material is applied to the lithium ion battery as a negative electrode material, and the obtained lithium ion battery not only has excellent first effect and cycle performance, but also has relatively good discharge capacity, rate capability and dynamic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite graphite material and a preparation method, application and a lithium ion battery thereof. Background Art

[0002] Although graphite materials have become commercial negative electrode materials, as the market's requirements for lithium-ion battery performance become increasingly stringent, the energy density, compaction density, and first-cycle charge and discharge efficiency of graphite materials still need to be continuously improved. At present, surface coating (carbon materials, metal materials, inorganic compounds) is commonly used to improve the comprehensive performance of graphite negative electrodes. Chinese patent application CN114628659A discloses a graphite negative electrode composite material for power batteries, the core of which is graphite and the outer shell is Li 5 FeO 4 The graphite anode composite material improves the initial efficiency and rate performance of the anode material, but the preparation process is complicated and the coating uniformity is poor, which makes the core coating integrity of the material low and easy to contact with the electrolyte, resulting in poor cycle stability of the material. In order to further improve the cycle performance and initial efficiency of the material, it is necessary to explore new coating methods. Summary of the invention

[0003] In order to solve the defects of poor cycle performance and initial efficiency of lithium ion batteries using graphite materials as negative electrode materials in the prior art, the present invention provides a composite graphite material and its preparation method, application and lithium ion battery. The composite graphite material is used as a negative electrode material in a lithium ion battery, and the obtained lithium ion battery not only has excellent initial efficiency and cycle performance, but also has good discharge capacity, rate performance and kinetic performance.

[0004] The present invention adopts the following technical solutions to solve the above technical problems:

[0005] The present invention provides a composite graphite material, which comprises graphite. The surface of the graphite is provided with a coating layer, and the coating layer comprises hard carbon and LiF. The material is characterized in that the hard carbon and LiF are connected by a covalent bond.

[0006] In the present invention, the thickness of the coating layer is 60-200 nm.

[0007] The present invention provides a method for preparing a composite graphite material, which comprises the following steps:

[0008] S1, subjecting a mixture of lithium fluoroalkylsulfonyl imide, biochar and solvent to a mixed solvent thermal reaction, filtering, and obtaining a filtrate as a coating agent;

[0009] S2, mixing the coating agent with graphite to obtain a precursor; the mass ratio of the coating agent to the graphite is 1: (5-50);

[0010] S3, carbonizing the precursor.

[0011] In some preferred embodiments, the mixed material in step S1 is lithium fluoroalkylsulfonyl imide, biochar and solvent.

[0012] In some specific embodiments, the lithium fluoroalkylsulfonyl imide in step S1 is lithium bistrifluoromethanesulfonyl imide, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide or lithium 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonyl imide (LiHFDF).

[0013] In the present invention, the biochar in step S1 refers to a carbon-rich solid substance produced by thermochemical conversion of biomass under oxygen-limited or oxygen-free conditions.

[0014] In some specific embodiments, the biochar in step S1 is one or more of corn straw, wheat straw, rice straw, peanut straw, peanut shell, walnut husk and rice husk.

[0015] In the present invention, the solvent in step S1 can be a solvent commonly used in the art.

[0016] In some preferred embodiments, the solvent in step S1 is one or more of ethanol, methyl ether, ethyl ether, propyl ether and water.

[0017] In some specific embodiments, the solvent in step S1 is an ethanol-water solution, wherein the volume ratio of the ethanol to water is preferably 1:(0.5-10), for example, 1:1 or 1:6.

[0018] In some specific embodiments, the mass ratio of the lithium fluoroalkylsulfonyl imide to the biochar in step S1 is 1:(0.1-100), preferably 1:(10-50), for example 1:25, 1:30 or 1:35.

[0019] In some specific embodiments, the concentration of the lithium fluoroalkylsulfonyl imide in step S1 is 1-10 mg / mL, for example, 3.3 mg / mL.

[0020] The concentration unit of lithium fluoroalkylsulfonyl imide is mg / mL, which means: the mass (mg) of lithium fluoroalkylsulfonyl imide added per 1 mL of solvent.

[0021] In some specific embodiments, the concentration of the biochar in step S1 is 50-1000 mg / mL, for example, 83.3 mg / mL, 116.7 mg / mL or 833 mg / mL.

[0022] The unit of biochar concentration is mg / mL, which means: the mass (mg) of biochar added per 1 mL of solvent.

[0023] In some preferred embodiments, the temperature of the solvothermal reaction in step S1 is 200-350°C, for example, 230°C or 300°C.

[0024] In some preferred embodiments, the heating rate of the solvothermal reaction in step S1 is 1-5°C / min, for example, 2°C / min.

[0025] The heating rate refers to the rate at which the temperature rises from the initial temperature to the desired temperature.

[0026] In some preferred embodiments, the solvent thermal reaction time in step S1 is 5-10 h, for example, 7 h, 8 h or 9 h.

[0027] In the present invention, the graphite in step S2 can be artificial graphite and / or natural graphite. Further, the artificial graphite is single-particle artificial graphite.

[0028] In some specific embodiments, the graphite in step S2 is artificial graphite, and the D50 particle size of the artificial graphite is 5-20 μm, for example, 8 μm or 11.5 μm.

[0029] In the present invention, the mass ratio of the coating agent to graphite in step S2 is preferably 1:(5-30), for example, 1:10, 1:15 or 1:20.

[0030] In the present invention, the mixing in step S2 can be performed in a conventional manner in the art, such as stirring.

[0031] In some specific embodiments, the mixing method in step S2 is stirring.

[0032] Preferably, the stirring time is 0.5-2h; preferably, the stirring temperature is 20-30°C, such as room temperature, i.e., 25°C.

[0033] In some specific embodiments, the mixing in step S2 further includes a fusion process.

[0034] Preferably, the fusion process is performed using a fusion machine; more preferably, the rotation speed of the fusion machine is 500-950 r / min, and the fusion time is 5-15 min.

[0035] Preferably, the fusion treatment is carried out at room temperature.

[0036] In the present invention, the room temperature is 20-40°C, for example 25°C.

[0037] In the present invention, the temperature of the carbonization treatment in step S3 is preferably 600-900°C.

[0038] In some specific embodiments, the heating rate of the carbonization treatment is 2-5°C / min.

[0039] In some specific embodiments, the carbonization treatment time is 2-6 hours, for example, 3 hours.

[0040] In some specific embodiments, the carbonization treatment is performed under the protection of nitrogen or argon.

[0041] The present invention provides a composite graphite material, which is prepared by the above-mentioned method for preparing the composite graphite material.

[0042] The present invention provides an application of the composite graphite material as described above as a negative electrode material in a lithium ion battery.

[0043] The present invention also provides a lithium ion battery, which comprises the composite graphite material as described above.

[0044] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0045] The reagents and raw materials used in the present invention are commercially available.

[0046] The positive and progressive effects of the present invention are:

[0047] (1) The present invention obtains a filtrate rich in carbon and LiF by solvent thermal reaction of lithium fluoroalkylsulfonyl imide and biochar, which is then mixed with a graphite material and subsequently carbonized to coat the surface of the graphite precursor with a carbon layer containing hard carbon and LiF connected by covalent bonds. The carbon layer has good coating uniformity, improves electrical conductivity and has a certain mechanical stability, which can inhibit volume expansion during the cycle process, thereby improving the overall electrochemical performance.

[0048] (2) The coating layer of the LiF-doped carbon-coated graphite composite material prepared by the present invention evenly disperses LiF, and the carbon layer containing LiF can induce the formation of a solid electrolyte membrane (SEI membrane) with good interface stability. At the same time, the insulating property of lithium fluoride can prevent the further decomposition of the electrolyte and the continuous loss of lithium ions, thereby achieving a simultaneous improvement in the initial efficiency and cycle stability.

[0049] (3) The composite graphite material prepared by the present invention has an initial efficiency of more than 95%, a DC impedance (DCIR) of less than 5.8Ω and an AC impedance (EIS) of less than 7.5Ω, and a capacity retention rate of more than 95% after 1000 cycles, and has excellent rate performance.

[0050] (4) The present invention can be processed by industrial equipment such as a fusion machine and a tubular furnace. The method is simple and easy to carry out large-scale production in factories.

[0051] (5) The present invention can use various waste biochars as carbon sources, such as rice husks, fruit shells, straw, water-soluble starch, etc. The raw materials are widely available and the resources are abundant. Using biochar as a carbon source is not only a way to achieve waste utilization, but also conforms to the concept of green and sustainable development. In addition, waste biomass is low-cost and can be produced on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is the SEM image of the composite graphite material prepared in Example 1. DETAILED DESCRIPTION

[0053] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0054] Lithium bis(trifluoromethanesulfonyl)imide (CAS No. 90076-65-6)

[0055] Single-particle artificial graphite: The needle coke is subjected to coarse crushing, fine grinding and spheroidization treatment in sequence, and the material obtained by spheroidization is subjected to graphitization and screening treatment in sequence to obtain single-particle artificial graphite. All embodiments and comparative examples of the present application use this single-particle artificial graphite, and the D50 particle size of the single-particle artificial graphite is 11.5 μm.

[0056] Example 1

[0057] S1. Dissolve 200 mg of lithium bis(trifluoromethanesulfonyl)imide and 5 g of rice husk in 60 mL of ethanol-water solution (volume ratio of ethanol to water is 1:1), transfer the solution to a 150 mL polytetrafluoroethylene reactor, heat to 200 °C (heating rate is 10 °C / min), perform solvent thermal reaction for 8 h, filter after the reaction to obtain a filtrate, which is the coating agent;

[0058] S2, adding 200 g of the coating agent obtained in step S1 and 2 kg of single-particle artificial graphite (i.e., the mass ratio is 1:10) into a fusion machine after stirring at room temperature for 30 min, and fusion at 950 r / min for 5 min to obtain a precursor;

[0059] S3. Transfer the precursor obtained in step S2 to a tubular furnace protected by Ar atmosphere, heat it to 600° C. at a rate of 10° C. / min, and perform carbonization treatment for 2 h to obtain a composite graphite material.

[0060] Example 2

[0061] S1. Dissolve 200 mg of lithium bis(trifluoromethanesulfonyl)imide and 50 g of water-soluble starch in 60 mL of ethanol-water solution (volume ratio of ethanol to water is 2:1), transfer the solution to a 150 mL polytetrafluoroethylene reactor, heat to 230°C (heating rate is 10°C / min), perform solvent thermal reaction for 5 h, filter after reaction, and obtain a filtrate, which is the coating agent;

[0062] S2, adding 100 g of the coating agent obtained in step S1 and 2 kg of single-particle artificial graphite (i.e., the mass ratio is 1:20) into a fusion machine after stirring at room temperature for 30 min, and fusion at 950 r / min for 5 min to obtain a precursor;

[0063] S3. Transfer the precursor obtained in step S2 to a tubular furnace protected by Ar atmosphere, heat it to 600° C. at a rate of 10° C. / min, and perform carbonization treatment for 2 h to obtain a composite graphite material.

[0064] Example 3

[0065] S1. Dissolve 200 mg of lithium bis(trifluoromethanesulfonyl)imide and 7 g of crushed straw in 60 mL of ethanol-water solution (volume ratio of ethanol to water is 2:1), transfer the solution to a 150 mL polytetrafluoroethylene reactor, heat to 300 °C (heating rate is 10 °C / min), perform solvent thermal reaction for 8 h, filter after reaction, and obtain the filtrate, which is the coating agent.

[0066] S2, 40g of the coating agent obtained in step S1 and 2kg of single-particle artificial graphite (mass ratio of 1:50) were mixed evenly and added into a fusion machine, and fused at 500 r / min for 15 minutes to obtain a precursor;

[0067] S3. The precursor obtained in step S2 is heated to 900° C. at a rate of 10° C. / min in a tubular furnace protected by Ar atmosphere, and carbonized for 3 hours to obtain a composite graphite material.

[0068] Example 4

[0069] The difference from Example 3 is that: 200 g of filtrate and 2 kg of artificial graphite (ie, the mass ratio is 1:10) are added in step S2.

[0070] Example 5

[0071] The difference from Example 3 is that: 133 g of filtrate and 2 kg of artificial graphite (ie, the mass ratio is 1:15) are added in step S2.

[0072] Example 6

[0073] The difference from Example 3 is that: 200 mg of lithium bis(trifluoromethanesulfonyl)imide and 20 mg of crushed straw (ie, the mass ratio is 10:1) are added in step S1.

[0074] Example 7

[0075] The difference from Example 3 is that 400 g of coating agent and 2 kg of artificial graphite (i.e., the mass ratio is 1:5) are added in step S2.

[0076] Example 8

[0077] The difference from Example 3 is that lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide is used to replace lithium bis(trifluoromethanesulfonyl)imide in step S1.

[0078] Comparative Example 1

[0079] It is only a single particle of artificial graphite with a D50 particle size of 11.5μm.

[0080] Comparative Example 2

[0081] 2kg of single-particle artificial graphite and 200g of coal tar (as a coating agent) were put into a vertical plowshare mixer and mixed for 1 hour. After discharging, they were transferred to a horizontal heating and stirring reactor, heated to 600°C at a heating rate of 5°C / min, kept warm for 3 hours, and discharged after cooling to room temperature. They were then put into a roller kiln for heat treatment (temperature of 1150°C, time of 20 hours, heating rate of 10°C / min) and screening treatment in sequence to obtain artificial graphite with a D50 particle size of 11.5μm.

[0082] Comparative Example 3

[0083] The difference from Example 3 is that the lithium bis(trifluoromethanesulfonyl)imide in step S1 is replaced by LiF. The other steps and conditions are the same as those in Example 3.

[0084] Comparative Example 4

[0085] The difference from Example 3 is that the lithium bis(trifluoromethanesulfonyl)imide in step S1 is replaced by Li 5 FeO 4 The other steps and conditions are the same as those in Example 3.

[0086] Comparative Example 5

[0087] The difference from Example 3 is that 1 kg of coating agent and 2 kg of artificial graphite (ie, the mass ratio is 1:2) are added in step S2. The other steps and conditions are the same as those in Example 3.

[0088] Comparative Example 6:

[0089] The difference from Example 3 is that the biomass charcoal straw in step (1) is replaced by coal tar pitch, and the other steps and conditions are the same as those in Example 3.

[0090] Effect Example 1

[0091] Material morphology characterization: The SEM image of the hard carbon material was obtained using a ZEISS scanning electron microscope. The SEM image of the composite graphite material obtained in Example 1 is as follows: Figure 1 As shown. Figure 1 It can be seen that the composite graphite material obtained in Example 1 of the present invention includes graphite, and a coating layer is provided on the surface of the graphite. The thickness of the coating layer can be calculated by the scale in the figure to be 60-200 nm. Through further characterization, the coating layer includes hard carbon and LiF, and the hard carbon and LiF are connected by covalent bonds.

[0092] Effect Example 2

[0093] The composite graphite materials in Examples 1-8 and Comparative Examples 1-6 were used as negative electrode materials to prepare lithium ion batteries.

[0094] The preparation method of lithium-ion battery is as follows: the above negative electrode material, N-methylpyrrolidone containing 6% to 7% polyvinylidene fluoride and conductive carbon black are mixed evenly in a mass ratio of 91.6:6.6:1.8, and coated on a copper foil with a thickness of 9μm, and the coated electrode is placed in a vacuum drying oven (110℃ 4h) for vacuum drying for use. The metal lithium sheet is used as the counter electrode, and 1mol / L LiPF 6 As the electrolyte, a mixed solution of EC, DEC and DMC with a volume ratio of 1:1:1 was used as the solvent, and a polypropylene porous membrane was used as the separator. The above materials were assembled into a CR2032 button cell in an argon-filled glove box.

[0095] The lithium-ion battery prepared above was subjected to the following electrochemical performance tests:

[0096] Among them, the electrochemical performance test was carried out on an American Arbin BT2000 battery tester, with a charge and discharge voltage range of 5mV to 2.0V, a charge and discharge rate of 0.1C, and a temperature of room temperature.

[0097] (1) Charge / discharge capacity and initial efficiency

[0098] The test method for charging capacity is: discharge at 0.1C constant current to 5mV, and charge at 0.1C constant current to 2V to obtain the capacity as the charging capacity;

[0099] The test method of discharge capacity is: charge to 2V at 0.1C constant current, discharge to 5mV at 0.1C constant current, and the obtained capacity is the discharge capacity;

[0100] The first effect can be calculated by the following formula:

[0101] First effect = discharge capacity / charge capacity.

[0102] (2) Capacity retention after 1000 cycles

[0103] Test method: Discharge to 5mV at 0.1C constant current, charge to 2V at 0.1C constant current, discharge to 5mV at 0.1C constant current, and then test the charging capacity of the battery after 1 and 1000 cycles respectively;

[0104] The capacity retention rate can be calculated by the following formula:

[0105] Capacity retention rate = 1000th charge capacity / first charge capacity

[0106] (3) Rate performance

[0107] The rate performance test method is: charge to 2V at 0.1C constant current, and discharge to 5mV at 0.1C constant current, recorded as 0.1C / 0.1C;

[0108] 0.2C / 0.1C, 0.5C / 0.1C, 1C / 0.1C, 2C / 0.1C, 3C / 0.1C, 0.2C / 0.1C are tested with the same steps.

[0109] (4) DC impedance (DCIR)

[0110] DCIR refers to the phenomenon that voltage rebound occurs after the battery is discharged due to polarization.

[0111] The test conditions of DC impedance are: intermittent discharge at a constant current of 1A for 20 minutes, and the internal resistance of the battery is calculated by the difference between the voltage before the end of discharge and the voltage after the discharge is stabilized after 5 minutes of standby, R = ∆U / I, where ∆U is the voltage difference, R is the DC resistance, and I is the discharge current. A smaller DC impedance indicates better dynamic performance.

[0112] (5) Electrochemical impedance spectroscopy (EIS)

[0113] Electrochemical impedance spectroscopy (EIS) involves superimposing a low-amplitude sinusoidal voltage of 5 mV (usually 5 or 100 mV) on the open circuit voltage and detecting the current response in the frequency range of 10 mHz-100 kHz.

[0114] The AC impedance can be calculated by the following formula: Z = R + jX

[0115] Where R is the resistance (real part), X is the reactance (imaginary part), and j is the imaginary unit. The smaller the AC impedance, the better the dynamic performance.

[0116] The above test results are listed in Table 1, Table 2 and Table 3. Table 1 presents the test results of discharge capacity, initial efficiency and capacity retention rate after 1000 cycles of Examples 1-8 and Comparative Examples 1-5; Table 2 presents the rate test results of Examples 1-8 and Comparative Examples 1-5 at different rates; Table 3 presents the DCIR and EIS test results of Examples 1-8 and Comparative Examples 1-5.

[0117] Table 1:

[0118] serial number Discharge capacity (mAh / g) First effect (%) Capacity retention rate after 1000 weeks (%) Example 1 349.20 95.21 97.3 Example 2 351.75 95.53 97.9 Example 3 349.42 96.29 95.2 Example 4 351.20 95.55 96.2 Example 5 350.32 96.11 95.6 Example 6 349.47 96.37 97.1 Example 7 348.32 96.32 95.6 Example 8 349.6 95.67 95.3 Comparative Example 1 351.98 94.51 94.2 Comparative Example 2 349.20 93.03 94.7 Comparative Example 3 350.13 93.45 93.2 Comparative Example 4 346.30 93.16 92.6 Comparative Example 5 344.26 96.32 97.1 Comparative Example 6 344.11 93.28 93.1

[0119] Table 2:

[0120] serial number 0.1C / 0.1C 0.2C / 0.1C 0.5C / 0.1C 1C / 0.1C 2C / 0.1C 3C / 0.1C 0.2C / 0.1C Example 1 97.7% 93.2% 79.2% 56.3% 18.6% 6.3% 91.7% Example 2 97.4% 89.6% 77.5% 53.9% 15.9% 5.2% 91.5% Example 3 97.1% 89.5% 73.2% 52.4% 16.5% 5.4% 92.1% Example 4 97.2% 87.1% 76.9% 52.3% 15.2% 5.1% 91.1% Example 5 98.0% 95.6% 82.6% 57.1% 17.9% 6.8% 93.9% Example 6 98.5% 96.1% 83.6% 59.3% 17.6% 6.0% 94.4% Example 7 97.8% 92.4% 75.7% 58.9% 18.3% 6.4% 91.6% Example 8 97.9% 94.0% 72.1% 48.5% 14.5% 5.3% 94.9% Comparative Example 1 94.7% 88.8% 75.1% 52.1% 15.4% 5.3% 92.2% Comparative Example 2 96.0% 91.5% 66.3% 30.3% 8.3% 3.8% 89.6% Comparative Example 3 94.8% 88.2% 71.3% 37.8% 9.1% 3.7% 90.9% Comparative Example 4 95.8% 91.1% 72.6% 36.8% 8.1% 3.6% 90.7% Comparative Example 5 93.5% 87.5% 64.0% 25.1% 5.2% 3.2% 86.7% Comparative Example 6 93.1% 88.3% 66.2% 26.9% 5.8% 3.1% 86.1%

[0121] Table 3:

[0122] serial number DCIR (Ω) EIS (Ω) Example 1 4.19 3.29 Example 2 4.47 3.34 Example 3 4.47 3.66 Example 4 4.59 5.29 Example 5 5.74 6.47 Example 6 3.89 3.21 Example 7 4.14 4.54 Example 8 4.76 7.26 Comparative Example 1 5.74 6.47 Comparative Example 2 5.91 6.97 Comparative Example 3 6.89 7.27 Comparative Example 4 6.13 7.38 Comparative Example 5 7.17 7.31 Comparative Example 6 7.13 7.61

[0123] From the above test results, we can get:

[0124] (1) The LiF-doped carbon-coated graphite composite materials obtained by the simple and environmentally friendly preparation method in Examples 1-8 of the present invention have significantly improved initial efficiency. This may be because the LiF-containing carbon layer can induce the formation of a SEI film with good interface stability. At the same time, the insulating property of lithium fluoride can prevent the further decomposition of the electrolyte and the continuous loss of lithium ions, thereby achieving an improved initial efficiency.

[0125] (2) The carbon coating layer formed by the coating agent in Examples 1-8 of the present invention will cause a slight decrease in capacity, but the rate performance is significantly improved. Among them, the carbon-coated graphite negative electrode material prepared using water-soluble starch as the carbon source in Example 6 has the most obvious effect on improving the rate performance. This shows that the carbon layer containing LiF provides a faster electron / ion transmission channel for lithium ions.

[0126] (3) It can be seen from Examples 3-8 that as the mass ratio of the coating agent to the artificial graphite increases, the DCIR and EIS values ​​of the obtained carbon-coated graphite negative electrode material gradually decrease, indicating that the carbon layer containing LiF is beneficial to improving the ionic conductivity of the carbon-coated graphite negative electrode material. Among them, the DCIR and EIS impedance values ​​in Example 6 are smaller, indicating that it has better kinetic performance.

[0127] (4) Compared with Comparative Examples 3-4, the effect of using fluoroalkylsulfonyl imide lithium to prepare batteries for testing in Examples 1-8 is better than that of using other lithium salts. The reason may be that the present invention performs heat treatment under subcritical conditions, uses lithium bis(fluorosulfonyl)imide as the Li source and F source, wherein Li mainly exists in the form of Li-OH bonds and F mainly exists in the form of CF bonds, and coats the surface of the graphite negative electrode material with a carbon layer containing LiF. The coating layer can significantly improve the ion / electron conductivity of the material, and can also generate a stable inner layer of LiF-rich SEI film, reduce a large number of side reactions, improve the cycle performance of the material, and improve the first coulombic efficiency of the material. While using LiFLi 5 ,FeO 4 Inorganic lithium salts such as 2-nitrogen- ...

[0128] (5) Compared with Comparative Example 5, Examples 1-8 illustrate that the electrochemical performance and kinetic performance of the battery are better when the mass ratio of the coating agent to graphite is 1: (5-50). This is because if the amount of the coating agent is too high, the initial capacity efficiency will be lower, and if the amount is too low, a complete coating layer cannot be formed.

[0129] (6) The coating material used in Comparative Example 6 is coal tar pitch (i.e., soft carbon), while that used in Examples 1-8 is biomass carbon (i.e., hard carbon). Compared with Examples 1-8, the rate performance, first efficiency, and cycle stability of Comparative Example 6 are all poor, and the AC impedance is also relatively large.

[0130] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A composite graphite material, characterized in that: The invention comprises graphite, the surface of the graphite is provided with a coating layer, the coating layer comprises hard carbon and LiF, and the hard carbon and LiF are connected by a covalent bond.

2. The composite graphite material according to claim 1, characterized in that The coating layer has a thickness of 60-200 nm.

3. A method for preparing a composite graphite material, characterized in that: It includes the following steps: S1, subjecting a mixture of lithium fluoroalkylsulfonyl imide, biochar and solvent to a mixed solvent thermal reaction, filtering, and obtaining a filtrate as a coating agent; S2, mixing the coating agent with graphite to obtain a precursor; the mass ratio of the coating agent to the graphite is 1: (5-50); S3, carbonizing the precursor.

4. The method for preparing the composite graphite material according to claim 3, characterized in that: The S1 satisfies one or more of the following conditions: a. The mixture is lithium fluoroalkylsulfonyl imide, biochar and a solvent; b. The fluoroalkylsulfonyl lithium imide is one or more of lithium bistrifluoromethanesulfonyl imide, lithium (fluorosulfonyl) (perfluorobutylsulfonyl) imide and lithium 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonyl imide; c. The biochar is one or more of corn straw, wheat straw, rice straw, peanut straw, peanut shells, husks and rice husks; d. The solvent is one or more of ethanol, methyl ether, ethyl ether, propyl ether and water; Preferably, the solvent is an ethanol-water solution, wherein the volume ratio of the ethanol to water is preferably 1:(0.5-10), for example, 1:1 or 1:6; e. The mass ratio of the lithium fluoroalkylsulfonyl imide to the biochar is 1:(0.1-100), preferably 1:(10-50), for example 1:25, 1:30 or 1:35; f. The concentration of the lithium fluoroalkylsulfonyl imide is 1-10 mg / mL, for example 3.3 mg / mL; g. The concentration of the biochar is 50-1000 mg / mL, for example, 83.3 mg / mL, 116.7 mg / mL or 833 mg / mL.

5. The method for preparing the composite graphite material according to claim 3, characterized in that: In step S1, the solvent thermal reaction satisfies one or more of the following conditions ac: a. The solvothermal reaction temperature is 200-350 ℃, for example 230 ℃ or 300 ℃; b. The heating rate of the solvothermal reaction is 1-5°C / min, for example 2°C / min; c. The solvent thermal reaction time is 5-10h, for example 7h, 8h or 9h.

6. The method for preparing the composite graphite material according to claim 3, characterized in that: Step S2 satisfies one or more of the following conditions ad: a. The mass ratio of the coating agent to the graphite is 1:(5-30), for example 1:10, 1:15 or 1:20; b. The graphite is artificial graphite and / or natural graphite; the D50 particle size of the artificial graphite is 5-20 μm, for example, 8 μm; c. The mixing method is stirring; Preferably, the stirring time is 0.5-2h; Preferably, the stirring temperature is 20-30°C, for example, room temperature, i.e., 25°C; d. The mixing further comprises a fusion process; Preferably, the fusion process is performed using a fusion machine; more preferably, the rotation speed of the fusion machine is 500-950 r / min, and the fusion time is 5-15 min; preferably, the temperature of the fusion process is room temperature.

7. The method for preparing the composite graphite material according to claim 3, characterized in that: Step S3 satisfies one or more of the following conditions ad: a. The carbonization temperature is 600-900 ℃; b. The heating rate of the carbonization treatment is 2-5°C / min; c. The carbonization time is 2-6h, for example 3h; d. The carbonization treatment is carried out under the protection of nitrogen or argon.

8. A composite graphite material, characterized in that: The composite graphite material is prepared by the method for preparing the composite graphite material as claimed in claim 3.

9. Use of the composite graphite material as claimed in any one of claims 1 to 2 and 8 as a negative electrode material in a lithium ion battery.

10. A lithium ion battery, characterized in that: It comprises the composite graphite material as claimed in claim 1.

Citation Information

Patent Citations

  • Graphite negative electrode composite material for power battery and preparation method of graphite negative electrode composite material

    CN114628659A